The influence of educational factor capital on the tangible career outcomes of MBA graduates - Daut, Azizah; Mohd Mokhtar, Sany Sanuri; Pangil, Faizuniah (The Social Sciences Research Society, 2012)
By the year 2020, Malaysia hopes to achieve the main objective of becoming a high-income advanced nation through the launching of New Economic Model (NEM). To achieve this objective, the country needs quality human capital among its graduates that commensurate with higher tangible rewards. This study looks at the scholastic, social, cultural, and inner-value capital of individuals, gained during the attainment of MBA studies, and their relationships to the tangible career outcomes of salary gain, number of promotion, and managerial rank. 156 MBA alumni returned the self-administered online survey. Multinomial logistic regression is employed to test the hypotheses and the results are found to be partially supported. A major finding reveals that cultural capital is significantly associated with the likelihood of higher tangible career outcomes. Findings from this study allow educational providers and policy makers to have better understanding in assessing specific educational capital, gained through a specific educational program such as MBA, on tangible career success outcomes.